Sexually dimorphic melanin‐based colour polymorphism, feather melanin content, and wing feather structure in the barn owl (Tyto alba). (9th April 2013) - Roulin, Alexandre; Mangels, Jule; Wakamatsu, Kazumasa; Bachmann, Thomas
<x xml:space="preserve">Abstract</x> Feathers confer protection against biophysical agents and determine flying ability. The geometry and arrangement of the barbs, together with the keratin and pigments deposited in the feathers, determine the mechanical stability of the vane, and its stiffness and resistance to abrasive agents. In colour‐polymorphic species, individuals display alternative colour morphs, which can be associated with different foraging strategies. Each morph may therefore require specific flying abilities, and their feathers may be exposed to different abrasive agents. Feathers of differently coloured individuals may thus have a specific structure, and colour pigments may help resist abrasive agents and improve stiffness. We examined these predictions in the barn owl (Tyto alba), a species for which the ventral body side varies from white to dark reddish pheomelanic, and in the number and size of black spots located at the tip of the feathers. White and reddish birds show different foraging strategies, and the size of black feather spots is associated with several phenotypic attributes. We found that birds displaying a darker reddish coloration on the ventral body side deposit more melanin pigments in their remiges, which also have fewer barbs. This suggests that wear resistance increases with darkness, whereas feathers of lighter coloured birds may bend less easily. Accordingly, individuals displaying a lighter reddish coloration on the ventral body side, and those displaying larger black spots, displayed more black transverse bars on their remiges: as larger‐spotted individuals are heavier and longer‐winged birds also have more transverse bars, these bars may reduce feather bending when flying. We conclude that differently coloured individuals produce wing feathers of different strengths to adopt alternative behavioural and life history strategies. © 2013 The Linnean Society of London, Biological Journal of the Linnean Society, 2013, 109, 562–573.